Evaluating the Impact of Mass Surveillance Through Ethical Theories - Lähteenmäki, Camilla (My University, 2025)
This thesis explores the ethical implications of mass surveillance and the concept of the data double, framed through the lenses of deontology, consequentialism, and virtue ethics. Mass surveillance, encompassing technologies like facial recognition, AI, machine learning, and GPS tracking, presents significant challenges to privacy, autonomy, and societal trust. The thesis examines how these ethical theories assess the practices and consequences of mass surveillance, highlighting the interplay between individual rights, societal benefits, and moral character. To illustrate global implications, special attention is given to contemporary trends, such as the EU-U.S. Data Privacy Framework and China’s Social Credit System. The concept of the data double—a digital reflection of individuals—serves as a focal point to understand surveillance’s multifaceted impacts. The research underscores the interconnectedness of ethical considerations through critical analysis and offers practical recommendations for more ethically aligned surveillance practices.
Keywords: Mass Surveillance, Data Double, Deontology, Consequentialism, Virtue Ethics, Privacy, AI, Machine Learning, Facial Recognition, EU-U.S. Data Privacy Framework, Social Credit System, Ethics